An AM-FM model for motion estimation in atherosclerotic plaque videos - Murray, Víctor; Murillo, Sergio; Pattichis, Marios S.; Loizou, Christos P.; Pattichis, Constantinos S.; Kyriacou, Efthyvoulos C.; Nicolaides, Andrew N. (My University, 2008)
We present new multidimensional Amplitude-Modulation Frequency-Modulation (AM-FM) methods for motion estimation. For a single AM-FM component we show that the optical flow constraint leads to separate equations for amplitude modulation (AM) and frequency modulation (FM). We compare our approach with phase-based estimation developed by Fleet and Jepson and also the original optical flow method by Horn and Schunck. An advantage of the proposed method is that it provides for dense estimates that remain accurate over the entire video. We also present preliminary results on atherosclerotic plaques videos where the AM method appears to work best. © 2007 IEEE.
Keywords: Amplitude Modulation (AM); Frequency-Modulation (FM); Image motion analysis; Optical modulation